Cross-coupling vestibular stimulation: motion sickness and the vestibulo-sympathetic reflex - Romano, Fausto; Caramia, Nicoletta; Straumann, Dominik; Nalivaiko, Eugene; Bertolini, Giovanni (Journal of neurology, 2017)
Motion sickness is associated with a variety of autonomic symptoms, presumably due to proximity or functional interconnectivity between the autonomic centers in the brainstem and the vestibular system. A direct influence of the vestibular system on cardiovascular variables, defined as the vestibulo-sympathetic reflex, has been reported previously. Our aim was to investigate the sudomotor components of the autonomic responses associated with motion sickness during passive cross-coupling stimulation (“roll while rotating”). Healthy subjects ( n = 17) were rotated at 40°/s around an earth-vertical yaw axis alone and in combination with sinusoidal roll oscillations (0.2 Hz). Motion sickness was assessed verbally every minute using a 1–10 scale, while recording DC and AC skin conductance levels (SCL) from the forehead. Yaw rotation alone provoked neither motion sickness nor variations of forehead sweating. Yet during cross-coupling stimulation all subjects reported motion sickness. Higher motion sickness scores (>5) were associated with significantly higher amplitudes of AC-SCL events compared to the lower scores (0.22 ± 0.01 vs. 0.11 ± 0.01 µS, respectively). Frequency domain analysis of the AC-SCL events revealed a peak at 0.2 Hz, coinciding with the frequency of the chair rolls. The total power of AC-SCL signals did not match the trend of motion sickness scores across conditions. We conclude that: (1) although SCL is related to motion sickness, it does not follow the perceived sickness closely; (2) the discrepancy between SCL and motion sickness and the rhythmic AC-SCL events could reflect a sudomotor component of the vestibulo-sympathetic reflex.